がん治療関連心血管疾患に対する治療法確立を目指して－腫瘍循環器学の発展とこれから - 細田, 洋司; 上園, 保仁; 野中, 美希; 上野, 晋 (日本薬理学会年会要旨集, 2022)
Recently, a new interdisciplinary field called Cardio-Oncology/Onco-Cardiology has been established, which is due to the new focus on cardiac dysfunction and/or cardiovascular disease that cancer patients develop during cancer treatment. This Cancer Therapeutics-Related Cardiovascular Disease (CTRCD) has become widely recognized and efforts to overcome the CTRCD have begun worldwide. Doxorubicin, which is still widely used even with the development of newer anti-cancer and molecularly targeted drugs, is known to frequently develop cardiotoxicity dependent on cumulative doses. In addition, immune checkpoint inhibitors, anti-cancer drugs developed based on a completely different concept in recent years, have been reported to cause fulminant myocarditis, leading to death. Since the concept of CTRCD is expected to spread along with the development of novel anticancer drugs, basic to clinical research on CTRCD will be indispensable. In this study, we would like to summarize current knowledge on the etiology, outcome, therapeutic development of CTRCD, and discuss the development of novel therapeutic agents to prevent and treat CTRCD.